2019
DOI: 10.1016/j.jff.2019.103567
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative bioactivity against HT-29 colon cancer cells of a withanolides-rich extract from golden berry (Physalis peruviana L.) calyx investigated by Foodomics

Abstract: A comprehensive Foodomics study was carried out in this work to investigate the changes induced at gene and metabolite expression levels on HT29 colon cancer cell lines upon treatment with a bioactives-enriched extract from goldenberry calyx. As a result of the proposed multi-omics approach, the tested extract induced transcriptional activation of pro-apoptotic genes, and altered the expression of several genes related to the oxidative stress response in treated cancer cells. Metabolomics data confirm altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 71 publications
1
18
0
1
Order By: Relevance
“…This effect could be attributed to polyphenolic compounds such as the protocatechuic and chlorogenic acids, which were the main polyphenols that we quantified in all the above mentioned extracts. Previous studies report similar compounds in other Physalis varieties (Ballesteros‐Vivas, Alvarez‐Rivera, et al., 2019). Additionally, the above mentioned compound, through lipid oxidation inhibition, exerts antioxidant activity (Hur et al., 2003; Zhou et al., 1993).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This effect could be attributed to polyphenolic compounds such as the protocatechuic and chlorogenic acids, which were the main polyphenols that we quantified in all the above mentioned extracts. Previous studies report similar compounds in other Physalis varieties (Ballesteros‐Vivas, Alvarez‐Rivera, et al., 2019). Additionally, the above mentioned compound, through lipid oxidation inhibition, exerts antioxidant activity (Hur et al., 2003; Zhou et al., 1993).…”
Section: Discussionsupporting
confidence: 67%
“…(2018) reported that, in vitro, through inhibition of α‐glucosidase and, in vivo, by decreasing the insulin levels in pre‐diabetic rats, the P. alkekengi exert a hypoglycemic effect. This effect was attributed to the bioactive compounds such as terpenoids, phytosterols, tocopherols, phytochemicals, phenolic, withanolides, and sucrose esters (Ballesteros‐Vivas et al., 2019; Ballesteros‐Vivas, Alvarez‐Rivera, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These changes indicate that, although ROS levels and the main antioxidant enzyme activities are maintained in the presence of EO, significant decreases in glutathione and NADPH are produced, leading to a decrease in the antioxidant defense capacity of HepG2 cells. Previous works [ 49 , 50 ] have indicated that the shift in the cellular GSH-to-GSSG redox balance in favor of the oxidized species constitutes an important signal of cell impairment that can lead to the activation of the apoptotic signaling cascade, which may explain the results observed in the antiproliferative activity assay.…”
Section: Discussionmentioning
confidence: 99%
“…Os dois últimos extratos são o acetato de etila e o inespecífico, em que ambos foram feitos a base do cálice da planta e apresentaram efeito citotóxico, o extrato do cálice ainda apresentou a capacidade de aumentar a expressão de genes antioxidantes e pró-apoptóticos (Ballesteros-Vivas et al, 2019;Abou Baker & Rady, 2020).…”
Section: Demais Tipos De Extratounclassified